Ability, not heritage: Why expanding university access often fails to narrow intergenerational educational gaps - Thomas Åstebro; Henrik Hällerfors; Andreas Bergh; Joacim Tåg (Research Institute of Industrial Economics (IFN), 2025)
Many countries have established new local colleges to increase access to education for disadvantaged populations. However, many of these expansions have not reduced educational inequality. Drawing on evidence from a large-scale college expansion initiative, we find that increased college availability did not lead to a differential increase in attendance among students from parents with less education. Rather, the expanded access primarily benefited students with marginal academic ability. These results suggest that higher education enrollment is largely determined by inherent scholastic ability and that the expansion of higher education tends to attract students at the upper margin of this ability distribution.
Keywords: I23; I24; I28; J24; J62; 330; Intergenerational correlations; university expansion; access to education; higher education